REVITALISASI TARI LANGKAH DUA BELAS DI DESA SUNGAI BUNGKOK KECAMATAN KAPUAS KABUPATEN SANGGAU KALIMANTAN BARAT - Amelia, Dita; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe study was based on the disappearance of the Twelve Steps dance at Bungkok River Village, Kapuas District, Sanggau District, West Kalimantan. The objective of this research was to revitalize the Dance of Twelve at River Bungkok Village in order to live again among the people of Sungai Bungkok village environment. This research raised the problem that is about how the activities, the process of the activities, and results of the revitalization activities of the Twelve Steps in Bungkok River village, Kapuas Sub-district, Sanggau District, West Kalimantan. The result of this research was dissect the dance form of Twelve Steps by re-displaying the Twelve Steps dance using the accompaniment of the music and the costume of the dance in the village of Sungai Bungkok. The presence of local people who witnessed the performance of this Twelve dance, the researcherfelt that the revitalization was supported by the local community so it can be known in the village environment of Sungai Bungkok. Until now the Twelve Steps dance was still taught to other dancers friends in order to preserve one of the cultural traditions dance that is located in the village of Sungai Bungkok. This is what makes the researcherfelt that the research conducted by the researcher related to the revitalization of Twelve steps dance in Bungkok River village, Kapuas Sub-district, Sanggau District, West Kalimantan successful and running smoothly.Â Keywords : revitalization, dance Step Twelve, Sanggau District